2023
DOI: 10.1007/s10103-022-03704-y
|View full text |Cite
|
Sign up to set email alerts
|

An update on fractional picosecond laser treatment: histology and clinical applications

Abstract: Picosecond lasers have a very short pulse duration and a high peak power density. When fractional optical delivery systems are attached to picosecond lasers, they generate an array of concentrated microspots with a high fluence surrounded by areas with a low fluence. This article discusses the histologic characteristics and clinical applications of fractional picosecond laser treatment. Fractional picosecond laser produces laser-induced optical breakdown (LIOB) and laser-induced cavitation (LIC) in the epiderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…[15][16][17] FxPico causes LIOB-induced epidermal damage, which in turn triggers the release of growth factors, chemokines, and cytokines, initiating dermal remodeling. 10,20 Our specimens displayed similar histological changes to those of atrophic acne scars, 10,[21][22][23][24] verifying previous findings that the improvement of atrophic surgical scars is due to the production of new collagen, elastic tissue, and dermal mucin. Regarding the mechanism of FxPico on hypertrophic scars, the exact mechanism is yet to be proven.…”
Section: Discussionsupporting
confidence: 85%
“…[15][16][17] FxPico causes LIOB-induced epidermal damage, which in turn triggers the release of growth factors, chemokines, and cytokines, initiating dermal remodeling. 10,20 Our specimens displayed similar histological changes to those of atrophic acne scars, 10,[21][22][23][24] verifying previous findings that the improvement of atrophic surgical scars is due to the production of new collagen, elastic tissue, and dermal mucin. Regarding the mechanism of FxPico on hypertrophic scars, the exact mechanism is yet to be proven.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, increased dendritic cells were present in the PSAL with DLA treated side in one patient, suggesting laser therapy might have worsened disease activity. When 755‐nm PSAL with DLA is applied to the skin, the LIOB produces tiny lesions within the epidermis 20 . In some studies, the LIOB lesions in the basement membrane were observed to be filled with blood, and then histologically confirmed to be due to hemorrhage in the adjacent dermis, 19 so we hypothesize that the PSAL‐induced LIOBs may contribute to basement membrane disruption which allows the epidermal melanocytes to migrate into the dermis, thus appearing as melanophages or free melanin, We also observed increased dendritic cells in this patient on the PSAL side, which may contribute to reducing the treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, the shorter pulse duration of picosecond lasers compared to the nanosecond duration of QSNYL leads to higher photomechanical effects on the target chromophores and therefore more effective damage to the target tissue 17 . DLA induced laser‐induced optical breakdown (LIOB) minimizes thermal damage to the surrounding tissue while resulting in localized balls of hot plasma 18–20 However, picosecond lasers with or without a DLA have demonstrated varying efficacy for treating melasma in different studies 17,18,21,22 . a study by Lin et al, they treated melasma in Asians using PSAL with DLA, and the average MASI gradually and considerably decreased while the photoaging features improved until the 1‐year follow‐up, but after this time point the improvement gradually regressed 21 .…”
Section: Discussionmentioning
confidence: 99%
“…This barotrauma leads to dermis modifications that result in neoelastinogenesis and neocollagenesis, also resulting in improving the scar's aesthetics. [10][11][12] In this study, we aimed to assess the effectiveness of the picosecond Nd: YAG laser in comparison with fractional CO 2 laser in the management of postburn scars.…”
Section: Introductionmentioning
confidence: 99%
“…This barotrauma leads to dermis modifications that result in neoelastinogenesis and neocollagenesis, also resulting in improving the scar’s aesthetics. 10–12…”
Section: Introductionmentioning
confidence: 99%